DEVELOPING A PERFORMANCE ASSESSMENT OF KICKS IN THE COMPETITION CATEGORY OF PENCAK SILAT MARTIAL ARTS - Hariono, Awan; Rahayu, Tandiyo; Sugiharto, Sugiharto (Universitas Negeri Semarang, 2017)
The standard assessment of the competition category of Pencak Silat martial arts is not available in the Special Region of Yogyakarta (DIY). The objective of this research is to develop a performance assessment of the competition category of Pencak Silat martial arts in DIY based on a review of sports biomechanics. The method used in this study was research and development. The subjects were 6 fighters for the initial trial, 14 fighters for the small scale trial, and 53 fighters for the large scale trial. The content validity measure was employed to determine the validity of the data, while the product moment correlation was implemented to measure its reliability. The level of objectivity was analyzed with the interrater technique (Alpha coefficients). The results of the study are as the followings. 1) The performance assessment of the kicks in the competition category of Pencak Silat martial arts in the province of DIY is highly valid; 2) The performance assessment of the kicks in the competition category of Pencak Silat martial arts in DIY is highly reliable; 3) The performance assessment of the of the kicks in the competition category of Pencak Silat martial arts in DIY is highly objective; 4) The performance assessment of the of the kicks in the competition category of Pencak Silat martial arts in DIY is divided into five categories, namely: very good, good, average, poor, and very poor. The conclusion of this study is that the performance assessment of kicks in the competition category of Pencak Silat martial arts in DIY is classified into five categories. It is suggested that the generalization area may be broadened and it is necessary to involve more subjects in the large-scale trial.